A dynamic evaluation of central bank credibility - Cem Çakmaklı; Selva Demiralp (Koç University-TÜSIAD Economic Research Forum (ERF), 2020)
Central bank credibility is critical for the effectiveness of monetary policy. The measures of credibility that are based on the changes in actual inflation rate do not perform very well in environments of chronic inflation. We design an alternative measure that allows us to track the evolution of credibility in an inflationary environment. Credibility is defined as the central bank's ability to lower inflation expectations towards its inflation target via current interest rate decisions. We adopt a Bayesian set up to exploit this definition and document how credibility changes over time. Our measure differs from the existing measures that are based on the deviation of inflation expectations from the inflation target. We show that the latter tests may be too blunt in the EM context and either overlook marginal improvements in credibility or incorrectly attribute the temporary reductions in the inflation rate to improvements in credibility. Utilizing a time varying parameters modeling structure, we show that the credibility of the Central Bank of the Republic of Turkey (CBRT) has declined significantly over time. Potential reasons for this deterioration could be the CBRT's disappointing performance in hitting the inflation target and its exposure to political pressures. We apply our methodology to Brazil as well to highlight its advantages and draw a comparison to the existing literature.
Keywords: E52; E58; C32; 330; Credibility; inflation expectations; Central Bank of the Republic of Turkey; Unobserved component models; TVP-VAR; Central Bank of Brazil